The Anti-Termite Paper from Peanut Shell Waste with The Addition of Lemongrass Extract - Ahmadan Ilham Maulana; Ahmad Morteza Widjanarko; Hastu Hinayuan Narendra; Fauzan Ikhdan Nizaar; Tufail Najid (Jurnal Integrasi Sains dan Quran, 2022)
Based on Pusat Data dan Informasi Pertanian in 2020, the total production of peanuts in Indonesia reached 721 tons. Thus, if 20% of peanuts consist of shells, then peanut shell waste can reach 144 tons. If this is ignored, it will cause pollution problems. On the other hand, the use of paper which is known to be made of wood will be very detrimental, because the more paper is used, the higher the number of trees that must be cut down to meet demand. Peanut shell contains 63.5% cellulose. The amount is quite high considering that paper uses cellulose as a binder. In response to this, this study aims to determine the process of making termite-resistant paper made from peanut shell waste with the addition of lemongrass extract. This study uses a literature review to determine the content of peanuts which are used as the basic material for making paper and lemongrass extract which can repel termites. This study aims to solve the problem of paper that is easily damaged by termites. One of the ingredients in peanut shells is cellulose which functions as a binding agent. While the extract contained citronellal and geraniol. With these substances, the paper can become stronger and more resistant to termites.